The Climate Intelligent Organization : build an equitable and resilient future for the planet through AI-powered climate intelligence - Bassi, Iggy.; Chopra, Karan (Hoboken, USA: Chichester, UK: Wiley, 2025)
"This book is a practical guide for businesses looking to take action on climate change through a more complete and fuller understanding of the bigger paction of sustainability across the world. It focuses on the urgent need for reducing carbon emissions and the financial impacts of extreme weather events. The book explains climate risk in accessible language and offers actionable guidance for incorporating climate intelligence into decision-making. It also addresses recent changes in policy, including mandatory climate-related financial disclosures for businesses. This book fills a gap in existing resources by focusing on physical risk and adaptation rather than just the transition to a low-carbon economy. The book emphasizes the importance of open and transparent climate intelligence that is accessible to all -- truly successful climate change needs fully open climate intelligence. It highlights the interconnectedness of systems and how businesses may need to consider assets they don't even own. With its focus on practical guidance and accessible language, this book is a valuable resource for businesses looking to understand and address the financial impacts of climate change. Artificial intelligence and other new technologies help companies such as the author's to create high levels of climate intelligence, which in turn, enables organizations to work together to take action on climate change in a much more proactive way breeding effective results"
Keywords: Business Enterprises. -- Environmental Aspects; Sustainability -- Economic Aspects